PEMIMPIN YANG ADIL PERSPEKTIF KITAB AMSAL - Muti, Kristoforus Adeodatus; Senda, Siprianus S. (STIPAS Keuskupan Agung Kupang, 2021)
The just leader is very important to build up the common good (bonum commune) for the particular nation. Justice is the most important virtue in the social and political life because it touches human‟s nature as the social and political animal, as St. Thomas Aquinas ever thought. For Christians, the concept of the just leader could be found in the Scripture. The Proverbs is one of the literature book in the Old Testament that consists of a lot of life teachings and advices, including the virtue of the leader in the world. This essay will explore the concept of the just leader according the Proverbs‟ perspective. In Prov. 8:15-16, the concept of the just leader is grounded by the wisdom of God. “By me, the kings reign, and rules decree justice. By me princes rule, and nobles, all the judges of the earth.” There are some reflections that comes from the verses, i.e: the politics power comes from God and the leader‟s responsibility. These two reflections are in the way of St. Thomas Aquinas‟ concept concerning justice. According to St. Thomas, the just leader always directs himself and his people to the common good (bonum commune) and the unjust one just keep his own interest (bonum privatum). At the end of this essay, there are some relevant reflections of this concept of the just leader by Proverbs‟ perspective to the political development in Indonesia. There are a lot of problems come from the unjust leader who destroys the justice by doing corruption, collusion, and nepotism. This concept of the just leader could be the critical input to the politics‟ metanoia and give some positive perspective to the public to consider critically, especially to give their electoral votes.